The effect of specimen geometry on the compressive and tensile strengths of self-compacting rubberised concrete containing waste rubber granules. (October 2020) - Valizadeh, Afsaneh; Hamidi, Fatemeh; Aslani, Farhad; Shaikh, Faiz Uddin Ahmed
Abstract: Self-compacting rubberised concrete (SCRC) has been received great attention in recent years as an environmental remediation to not only fabricate sustainable and durable civil engineering structures, but also to take the very first steps towards resolving the issue of waste tyres abandoned in the nature. As a step forward in evaluating the structural performance of SCRC, the current research investigates the impacts of specimen size and specimen shape on the compressive and tensile strengths of SCRC containing 0%, 10%, and 20% crumb rubber aggregates (i.e., CSCC, SCRC10 and SCRC20) by means of both experimental and fracture mechanics-based theoretical approaches. Cubic specimens with dimension of 100 m m and 150 m m for assessing the compressive strength, cylindrical specimens with dimension of Φ 100 × 200 m m and Φ 150 × 300 m m for the both compressive and splitting tensile strengths measurement, and prism specimen with dimension of 100 × 100 × 400 m m for the flexural strength measurement were casted. The analytical study was performed based on the modified size effect low (MSEL) and adjusting its parameters by applying the experimental results, to establish the correlation between the mechanical properties of SCRC with the geometry of the structural element. Moreover, the relationship between the modulus of rupture and compressive strength of the SCRC has been also pioneered, based on the design codes recommended for the self-compacting concrete. The results show difference between the compressive strength of the cube-shaped specimen with standard cylinder specimen is more significant for mixes with 20% rubber aggregates rather than that for the SCRC with less than 20% rubber aggregate. Increasing the rubber aggregates content led to the significant size effect on the tensile strength of SCRC. The MSEL model predictions are in acceptable agreement for cubic specimen with the experimental data obtained for the CSCC and SCRC10 and for cylindrical specimen, the impact of varying the specimen size on the compressive strength weakened by increasing the rubber aggregate content.